Design and Use of Patient-Facing Electronic Patient-Reported Outcomes and Sensor Data Visualizations During Outpatient Chemotherapy - Christianna Bartel; Leeann Chen; Weiyu Huang; Qichang Li; Qingyang Li; Jennifer Fedor; Krina C Durica; Carissa A Low (JMIR Cancer)
AbstractThis study describes patients’ interaction with a personalized web-based visualization displaying daily electronic patient-reported outcomes and wearable device data during outpatient chemotherapy.